2020
DOI: 10.1177/0300891620923745
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility exploratory study of a novel modality of using patient-reported outcomes (PROsEXPLOR) in the real world

Abstract: Introduction: Patient-reported outcomes (PROs) can help clinicians better evaluate chemotherapy and immunotherapy toxicity based on patient perspectives. In this exploratory study, we tested a simplified PRO questionnaire (sPQ) in routine clinical practice and patient satisfaction with this tool. Methods: We included 16 items related to the main toxicities of chemotherapy and immunotherapy to be filled in by patients. A baseline sPQ was completed by patients before starting treatment and then in the interval b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[2][3][4] Previous experiences showed that the development of dedicated symptom management protocols help avoiding unnecessary medical encounters, ER visits and hospital admissions. 2,5,6 The primary care patient-centered medical home program provided a model built on a physician-led team that deals with disease management, nursing care coordination and patient education. Results from oncology patient-centered medical home models suggested a positive impact on cancer care quality and a significant reduction of both ER referrals and hospital admissions for patients undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Previous experiences showed that the development of dedicated symptom management protocols help avoiding unnecessary medical encounters, ER visits and hospital admissions. 2,5,6 The primary care patient-centered medical home program provided a model built on a physician-led team that deals with disease management, nursing care coordination and patient education. Results from oncology patient-centered medical home models suggested a positive impact on cancer care quality and a significant reduction of both ER referrals and hospital admissions for patients undergoing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%